2009
DOI: 10.1145/1517463.1517464
|View full text |Cite
|
Sign up to set email alerts
|

Enriching the spatial reasoning system RCC8

Abstract: One of the necessary basic concepts for the spatial data analysis in GIS is to determine the spatial relations between arbitrary geographical objects. In a two-dimensional space (IR 2 ), most existing topological models can distinguish the eight topological relations between two spatial regions A and B. These eight relations are written in the traditional form of the spatial reasoning system RCC8: DC, EC, EQ, PO, TPP, TPPi, NTPP and NTPPi. Because of the complexity of topological relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The well known 4-Intersection approach described in [16], [19], as well as the 9-Intersection approach as discussed in [20], and the Intersection and Difference (ID) model studied in [2], [3], [13], are proposed to formalize topological relations between simple and crisp regions.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The well known 4-Intersection approach described in [16], [19], as well as the 9-Intersection approach as discussed in [20], and the Intersection and Difference (ID) model studied in [2], [3], [13], are proposed to formalize topological relations between simple and crisp regions.…”
Section: Related Workmentioning
confidence: 99%
“…In [2], [3], [13], the topological complexity is considered as number of non-empty value in the topological relation model. It is hereof natural to define the topological complexity denoted by C T according to our topological relation model as follow: It is observed intuitively from the above list that the lowest topological complexity of the topological relations is the ones in the first group and the highest topological complexity of the topological relations is the ones in the eighth group.…”
Section: Topological Complexitymentioning
confidence: 99%
“…Then the topological distance between these two relations (UID 5 and UID 127 ) can be computed by (5) as follows:…”
Section: Vitopological Distancementioning
confidence: 99%
“…Then the topological distance is given by: Then the topological distance between these two relations (UID 63 and UID 136 ) can be computed by (5) as follows: Then the topological distance between these two relations (UID 84 and UID 103 ) can be computed by ( 5) as follows: In the properties from (1) to ( 6) of the topological distance, the notations UID k , UID m and UID n represent three topological relations obtained by the UID model, respectively. Compared to the definition of distance in metric space, it is easily observed that the topological distance is very similar to Manhattan distance.…”
Section: Vitopological Distancementioning
confidence: 99%
See 1 more Smart Citation